2016
DOI: 10.1016/j.eneco.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the energy-GDP elasticity: A sectoral approach

Abstract: This paper uses per capita data for 132 countries over 1960-2010 to estimate elasticities of sectoral energy use with respect to national gross domestic product (GDP). We estimate models in both levels and growth rates and use our estimates to sectorally decompose the aggregate energy-GDP elasticity. Our estimates show that residential energy use is very inelastic to GDP if primary solid biofuels are counted in energy use tallies, especially at low income levels. Residential use of electricity is more tightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 47 publications
(41 reference statements)
5
55
2
1
Order By: Relevance
“…There are also positive and significant coefficients for GDP per capita growth, confirming that electricity use increases as economies grow. The magnitude of the coefficients for log of GDP per capita and the growth of GDP per capita are similar to the findings of Burke and Csereklyei [54].…”
Section: Resultssupporting
confidence: 84%
“…There are also positive and significant coefficients for GDP per capita growth, confirming that electricity use increases as economies grow. The magnitude of the coefficients for log of GDP per capita and the growth of GDP per capita are similar to the findings of Burke and Csereklyei [54].…”
Section: Resultssupporting
confidence: 84%
“…This basic formulation follows Burke and Csereklyei [3] and Galeotti, Howarth and Lanza [9] in that it allows for a nonlinear effect of per capita income. The income elasticity of energy demand is, therefore, not constant and it can account for the decoupling of energy use from economic growth, possibly with a Kuznets curve behavior.…”
Section: Empirical Model and Results For Estimating Energy-gdp Elastimentioning
confidence: 99%
“…Burke and Csereklyei [3] use per capita data for 132 countries over 1960-2010 to estimate elasticities of sectoral energy use with respect to GDP. Models in both levels and growth rates are estimated resulting in a very income inelastic residential energy demand.…”
Section: Prices and Activitymentioning
confidence: 99%
“…Scholars of economic history and ecological economics have also shown that wealthier societies use more and "higher quality" energy per capita ( [34,75,76,42,77]). Most of the above theories deal with quantitative variables and can therefore be used to create quantitative models of energy systems and long-term scenarios of their change under different assumptions.…”
Section: A Cherp Et Almentioning
confidence: 99%